2007
DOI: 10.1158/0008-5472.can-06-2869
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Regulated Splice Variants and Novel Exons in Glial Brain Tumors Using Exon Expression Arrays

Abstract: Aberrant splice variants are involved in the initiation and/or progression of glial brain tumors. We therefore set out to identify splice variants that are differentially expressed between histologic subgroups of gliomas. Splice variants were identified using a novel platform that profiles the expression of virtually all known and predicted exons present in the human genome. Exon-level expression profiling was done on 26 glioblastomas, 22 oligodendrogliomas, and 6 control brain samples. Our results show that H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 40 publications
8
83
1
Order By: Relevance
“…The total number of detected splice variants between normal and cancer samples was comparable to other reports (33,45). The number was relatively low, which could be due to our conservative approach where only splice variants that occurred in most of the samples were identified; the stringent filtering applied to the data also lowered the number of splice variants detected.…”
Section: Discussionsupporting
confidence: 81%
“…The total number of detected splice variants between normal and cancer samples was comparable to other reports (33,45). The number was relatively low, which could be due to our conservative approach where only splice variants that occurred in most of the samples were identified; the stringent filtering applied to the data also lowered the number of splice variants detected.…”
Section: Discussionsupporting
confidence: 81%
“…We have recently demonstrated that exon-level profiling can detect exon-skipping mutants and splice variants (French et al, 2007;Schutte et al, 2008). In this study, we used these expression profiles to screen for fusion transcripts.…”
Section: Identifying a Novel Translocation Involving Est Ai364529 Andmentioning
confidence: 99%
“…Tissues adjacent to the paraffin-embedded hematoxylin and eosin-stained frozen sections were used for nucleic-acid isolation as described (French et al, 2007). For this study, we also isolated protein from the Trizol fraction according to the manufacturer's protocol (Invitrogen, Breda, The Netherlands).…”
Section: Rna Dna and Protein Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides further evidence that microarrays, and in particular exon arrays where probes are designed to detect individual exons, are excellent tools to discover novel alternative transcripts (Clark et al 2007, French et al 2007, Skotheim & Nees 2007, Rahman et al 2010, Menghi et al 2011. The exon-junction probe in our custom array was designed to target GenBank sequences deposited by Affymetrix as a result of RT-PCR validation of testisenriched exon array data (Clark et al 2007).…”
Section: Discussionmentioning
confidence: 87%